A galvanizing process for aviation anti-loosening nuts

By performing specific pretreatment and galvanizing process optimization on aviation lock nuts, and using technical means such as stabilizers and plating aids, the problem of difficulty in forming a uniform zinc layer in traditional galvanizing processes is solved, high-quality galvanizing layer formation is achieved, and the corrosion resistance and adhesion of the nut is improved.

CN119265501BActive Publication Date: 2025-04-01XIAN ZHITONG AVIATION TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411788072.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional galvanizing technology is difficult to form a uniform, dense and strong adhesion zinc layer on the surface of aviation lock nuts of special materials such as high-strength steel, stainless steel, titanium alloys, etc., especially at the threaded parts of the nuts and complex geometric shapes.

Method used

Specific pretreatment steps are adopted, including pickling with a stabilizer and a specific concentration of sulfuric acid to form an active metal layer, and promoting uniform wetting and deposition of zinc liquid through organic amine compounds and ionic liquids in the plating agent.

Benefits of technology

It significantly improves the flatness, corrosion resistance and adhesion of the galvanized layer, and meets the high-quality requirements of aviation lock nuts for galvanizing treatment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of aerospace engineering, and specifically discloses a galvanizing process for aviation anti-loosening nuts, comprising the following steps: S1. The nuts that have been preliminarily degreased are placed in a stabilizer and a pickling solution for pickling, pickling for 30-60 minutes at 50-80°C, stirring and turning the nuts in a timely manner during the pickling process, and neutralizing and washing with water after the pickling is completed; the pickling solution is sulfuric acid, and its mass concentration is 100-200g / L; the stabilizer includes a benzotriazole solution, a nonionic surfactant, and an ammonium chloride solution; S2. Hot-dip galvanizing: the pre-treated nuts are preheated and immersed in a plating aid for 5-8 minutes, and then quickly hot-dip galvanized at 438-443°C after being taken out; S3. After the galvanizing is completed, the nuts are taken out of the zinc liquid and cooled to room temperature. The process of the present application can be used for the galvanizing operation of aviation anti-loosening nuts, and its galvanized layer has the advantages of being flat and having good anti-corrosion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of aviation, and more specifically, to a galvanizing process for aviation anti-loosening nuts. Background Art

[0002] The aerospace engineering field has extremely high requirements for materials. Not only are the materials required to have mechanical properties such as high strength and high toughness, but they are also required to have good corrosion resistance and fatigue resistance. As one of the key fasteners in aerospace, the performance of aviation anti-loosening nuts directly affects the safety and reliability of the entire aerospace. Therefore, it is crucial to galvanize aviation anti-loosening nuts. Aviation anti-loosening nuts are usually made of high-performance materials such as high-strength steel, stainless steel, and titanium alloys. Galvanizing these materials can further improve the corrosion resistance and durability of the nuts. However, galvanizing faces many challenges for special materials such as high-strength steel, stainless steel, and titanium alloys. The high hardness, high melting point, and special chemical properties of these materials make it difficult for traditional galvanizing processes to form a uniform, dense, and highly adhesive zinc layer on the surface of the nut. Especially in the threaded parts and complex geometric shapes of the nut, the uniformity and integrity of the galvanized layer are even more difficult to guarantee.

[0003] In the related technologies, although various galvanizing treatment processes have been developed, such as electroplating and hot-dip galvanizing, these processes still have many shortcomings when processing aviation nuts made of special materials. For example, the electroplating process may make it difficult for the coating to adhere due to the high hardness of the material; hot-dip galvanizing may make it difficult for the zinc liquid to fully infiltrate the nut surface due to the high melting point of the nut material, resulting in uneven coating or defects, thus affecting the quality and performance of the coating. Summary of the invention

[0004] In order to improve the flatness and corrosion resistance of the galvanized layer of aviation anti-loosening nuts, the present application provides a galvanizing treatment process for aviation anti-loosening nuts.

[0005] The present application provides a galvanizing process for aviation anti-loosening nuts, which adopts the following technical solutions:

[0006] A galvanizing process for aviation anti-loosening nuts, comprising the following steps:

[0007] S1. The nuts that have undergone preliminary degreasing treatment are placed in a stabilizer and a pickling solution for pickling at 50-80°C for 30-60 minutes. The nuts are stirred and turned over in a timely manner during the pickling process. After the pickling is completed, the nuts are neutralized and washed with water to obtain pretreated nuts; the pickling solution is sulfuric acid with a mass concentration of 100-200g / L; the stabilizer includes a benzotriazole solution, a nonionic surfactant and an ammonium chloride solution;

[0008] S2. Hot dip galvanizing: The pre-treated nuts are preheated at a temperature of 200-300°C and then immersed in a plating agent for 5-8 minutes. After being taken out, they are quickly hot dip galvanized at 438-443°C.

[0009] S3. After the galvanizing is completed, the nut is taken out from the zinc liquid and quickly cooled to room temperature to obtain a galvanized aviation anti-loosening nut.

[0010] By adopting the above technical scheme, the hydrogen embrittlement of the steel matrix is ​​avoided through the stabilizer impregnation and pickling treatment in the pretreatment step, and a relatively low concentration of sulfuric acid is used for pickling, and the mass concentration of sulfuric acid is controlled between 100-200g / L, which effectively removes the oil, oxides and impurities on the surface of the nut, creating good conditions for the subsequent galvanizing process. Further plating aids can react chemically with the metal atoms on the surface of the nut to form an extremely thin active metal layer. This active metal layer can significantly increase the affinity of the nut surface to the zinc liquid, thereby promoting the infiltration of the zinc liquid, and the organic amine therein can coordinate and complex with the zinc ions to further promote the uniform deposition of zinc, ensuring the uniformity and density of the zinc plating layer.

[0011] By optimizing the galvanizing process parameters and adopting special processing steps, the galvanizing treatment process proposed in this application can significantly improve the adhesion between the zinc layer and the nut substrate, which helps to prevent the zinc layer from falling off due to factors such as vibration and impact during use.

[0012] Optionally, the stabilizer comprises the following raw materials in parts by weight: 1-3 parts of benzotriazole solution, 15-20 parts of nonionic surfactant and 10-15 parts of ammonium chloride solution.

[0013] By adopting the above technical solution, the stabilizer can adhere to the clean surface of the nut during the pickling process to form a dense protective film, thereby isolating it from the air and preventing the steel from being repeatedly oxidized and rusted after pickling. At the same time, the stabilizer can repair some oxidation defects on the surface, which helps the zinc liquid in the subsequent galvanizing process to quickly and fully infiltrate and react quickly to form a uniform zinc layer.

[0014] Optionally, the benzotriazole solution is prepared by dissolving benzotriazole in dimethylformamide, and its concentration is 0.8-1.0 mmol / L, and the mass concentration of the ammonium chloride solution is 20-25 g / L.

[0015] Optionally, the plating assistant solution comprises the following raw materials in parts by weight: 5-8 parts of potassium carbonate, 20-30 parts of zinc chloride, 40-60 parts of organic amine compounds, 10-14 parts of zinc plating brightener, 8-10 parts of polyoxyethylene ether sodium sulfate, and 10-12 parts of ionic liquid.

[0016] By adopting the above technical solution, zinc chloride is used as the main salt component in the plating solution, which is mainly responsible for providing zinc ions, which are indispensable in the galvanizing process. At the same time, the plating solution also contains organic amine compounds, which play multiple roles in the galvanizing process: they can significantly reduce the surface tension of the zinc liquid, making it easier for the zinc liquid to spread evenly on the surface of the nut; at the same time, the organic amine compounds can also react with the metal atoms on the surface of the nut to form a layer of active metal complexes, which further enhances the wettability of the nut surface to the zinc liquid. The added brightener can refine the grain structure of the zinc coating, making the surface of the zinc coating smoother and smoother, while improving its gloss and uniformity. As a non-ionic surfactant, polyoxyethylene ether sodium sulfate is added to the plating solution, using its good dispersing and emulsifying properties to further prevent the effective dispersion of oil and impurities on the surface of the nut, ensuring that the zinc liquid can smoothly infiltrate the surface of the nut, while increasing the stability of the plating solution to prevent it from stratification or precipitation during use.

[0017] As a new type of solvent, ionic liquid has the characteristics of low volatility, high stability and good solubility. It can not only further improve the stability of the plating agent, but also interact with the metal atoms on the surface of the nut to form a protective layer to prevent the nut from being over-oxidized or corroded during the galvanizing process.

[0018] These ingredients work together to give full play to their multiple functions such as cleaning, activation, reducing surface tension, providing zinc ions and forming a protective layer, so that the zinc liquid can quickly and evenly infiltrate the surface of the nut. Finally, a uniform and dense zinc coating will be formed on the surface of the nut. This zinc coating has good corrosion resistance and adhesion, meeting the high quality requirements of aviation anti-loosening nuts for zinc coating.

[0019] Optionally, the ionic liquid is 1-butyl-3-methylimidazolium chloroaluminate.

[0020] By adopting the above technical solution, 1-butyl-3-methylimidazolium chloroaluminate has excellent thermal stability, can remain liquid under high temperature conditions, and is not easy to decompose or deteriorate, thereby ensuring the long-term stability and use effect of the plating solution and improving the quality and bonding effect of the zinc plating layer.

[0021] Optionally, the organic amine compound is triethylamine.

[0022] By adopting the above technical solution, triethylamine can form a complex with zinc ions, which helps zinc ions to be stably and evenly deposited on the surface of the nut during the electroplating process. This can not only improve the uniformity and density of the zinc coating, but also reduce impurities and defects in the zinc coating process, thereby improving the quality of the zinc coating. At the same time, the addition of triethylamine can reduce the surface tension of the electroplating solution, making it easier for the zinc solution to spread on the surface of the nut. This helps to speed up the electroplating speed and improve the electroplating efficiency.

[0023] Optionally, 1-3 parts of dithiosuccinic acid are also added to the plating assistant.

[0024] By adopting the above technical scheme, there are two active thiol groups in the dimercaptosuccinic acid, which have a strong affinity with metals and can chelate with zinc ions to improve their stability, promote the stable and uniform deposition of zinc ions on the nuts, improve the adhesion of the coating, form a dense and uniform coating, and improve the stability of the zinc coating of the nuts.

[0025] Optionally, after cooling to room temperature in step S3, the surface of the nut is further passivated by immersing it in a passivation solution for 30-40 seconds and drying it naturally; the passivation solution is chromate.

[0026] By adopting the above technical solution, the passivation liquid can form a dense film on the surface of the zinc-plated layer of the nut. This film can effectively prevent the external corrosive media (such as oxygen, moisture and acidic substances) from contacting the metal substrate, thereby greatly extending the service life of the metal material and improving the corrosion resistance of the coating.

[0027] In summary, this application has the following beneficial effects:

[0028] 1. Since the present application adopts a specific pretreatment step, including pickling with a stabilizer and sulfuric acid of a specific concentration, the oil, oxides and impurities on the surface of the nut are effectively removed, creating good conditions for the subsequent galvanizing process.

[0029] 2. In this application, with the help of stabilizers and plating aids, the wettability problem encountered by high-strength, high-melting-point nuts during the galvanizing process is solved. The zinc liquid can quickly and evenly infiltrate the surface of the nut to form a strong galvanized layer, thereby enhancing the adhesion between the zinc layer and the nut substrate.

[0030] 3. The method of the present application significantly improves the efficiency and stability of the galvanizing process and the quality and consistency of the galvanized layer by adding a stabilizer to form a protective film, adopting an optimized plating solution formula, and performing a passivation treatment, thereby meeting the high quality requirements of the galvanizing treatment for aviation anti-loosening nuts. DETAILED DESCRIPTION

[0031] The present application is further described in detail below with reference to the embodiments.

[0032] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Example

[0033] Example 1

[0034] A galvanizing process for aviation anti-loosening nuts, characterized by comprising the following steps:

[0035] S1. The nuts that have undergone preliminary degreasing treatment are immersed in a stabilizer for 10 minutes, and then immersed in sulfuric acid with a mass concentration of 100 g / L for pickling. The nuts are pickled at 65°C for 45 minutes. The nuts are stirred and turned over in time during the pickling process. After the pickling is completed, the nuts are neutralized and washed with water to obtain pretreated nuts; the stabilizer includes 2 kg of benzotriazole solution, 15 kg of alkylphenol polyoxyethylene ether (non-ionic surfactant, OP-10) and 12 kg of ammonium chloride solution, which are mixed in sequence; the concentration of the benzotriazole solution is 1 mmol / L, and the mass concentration of the ammonium chloride solution is 20 g / L;

[0036] S2. Hot-dip galvanizing: The pre-treated nuts are preheated at 300°C and immersed in a plating agent for 5 minutes. After being taken out, they are quickly hot-dip galvanized at 440°C; the plating agent includes 6.5kg potassium carbonate, 25kg zinc chloride, 50kg triethylamine, 12kg benzyl acetone (zinc plating brightener), 9kg sodium polyoxyethylene ether sulfate, and 11kg 1-butyl-3-methylimidazole chloroaluminate;

[0037] S3. After the galvanizing is completed, take the nut out of the zinc solution, put it into water and quickly cool it to room temperature to obtain a galvanized aviation anti-loosening nut.

[0038] Example 2

[0039] A galvanizing process for aviation anti-loosening nuts, characterized by comprising the following steps:

[0040] S1. The nuts that have undergone preliminary degreasing treatment are immersed in a stabilizer for 15 minutes, and then immersed in sulfuric acid with a mass concentration of 150g / L for pickling. The nuts are pickled at 50°C for 30 minutes. During the pickling process, the nuts are stirred and turned over in time. After the pickling is completed, the nuts are neutralized and washed with water to obtain pretreated nuts; the stabilizer includes 1kg of benzotriazole solution, 20kg of alkylphenol polyoxyethylene ether (non-ionic surfactant, OP-10) and 10kg of ammonium chloride solution, which are mixed in sequence; the concentration of the benzotriazole solution is 0.08mmol / L, and the mass concentration of the ammonium chloride solution is 25g / L;

[0041] S2. Hot-dip galvanizing: The pre-treated nuts are preheated at 200°C and immersed in a plating agent for 8 minutes. After being taken out, they are quickly hot-dip galvanized at 438°C; the plating agent includes 5kg potassium carbonate, 20kg zinc chloride, 60kg triethylamine, 10kg benzyl acetone (zinc plating brightener), 8kg sodium polyoxyethylene ether sulfate, and 12kg 1-butyl-3-methylimidazole chloroaluminate;

[0042] S3. After the galvanizing is completed, take the nut out of the zinc solution, put it into water and quickly cool it to room temperature to obtain a galvanized aviation anti-loosening nut.

[0043] Example 3

[0044] A galvanizing process for aviation anti-loosening nuts, characterized by comprising the following steps:

[0045] S1. The nuts that have undergone preliminary degreasing treatment are immersed in a stabilizer for 15 minutes, and then immersed in sulfuric acid with a mass concentration of 200g / L for pickling. The nuts are pickled at 80°C for 30 minutes. During the pickling process, the nuts are stirred and turned over in time. After the pickling is completed, the nuts are neutralized and washed with water to obtain pretreated nuts; the stabilizer includes 3kg of benzotriazole solution, 17.5kg of alkylphenol polyoxyethylene ether (non-ionic surfactant, OP-10) and 15kg of ammonium chloride solution, which are mixed in sequence; the concentration of the benzotriazole solution is 0.09mmol / L, and the mass concentration of the ammonium chloride solution is 22.5g / L;

[0046] S2. Hot-dip galvanizing: The pre-treated nuts are preheated at 250°C and immersed in a plating agent for 6.5 minutes. After being taken out, they are quickly hot-dip galvanized at 443°C; the plating agent includes 8kg potassium carbonate, 30kg zinc chloride, 40kg triethylamine, 14kg benzyl acetone (zinc plating brightener), 10kg sodium polyoxyethylene ether sulfate, and 10kg 1-butyl-3-methylimidazole chloroaluminate;

[0047] S3. After the galvanizing is completed, take the nut out of the zinc solution, put it into water and quickly cool it to room temperature to obtain a galvanized aviation anti-loosening nut.

[0048] Example 4

[0049] A galvanizing treatment process for aviation anti-loosening nuts, which is different from Example 1 in that the plating solution in this example also includes 1 kg of dithiosulfate succinic acid.

[0050] Example 5

[0051] A galvanizing treatment process for aviation anti-loosening nuts, which is different from Example 1 in that the plating solution in this example also includes 2kg of dimercaptosuccinic acid.

[0052] Example 6

[0053] A galvanizing treatment process for aviation anti-loosening nuts, which is different from Example 1 in that the plating solution in this example also includes 3kg of dimercaptosuccinic acid.

[0054] Example 7

[0055] A galvanizing treatment process for aviation anti-loosening nuts, which is different from that of embodiment 1 in that it comprises the following steps:

[0056] S1. The nuts that have undergone preliminary degreasing treatment are immersed in a stabilizer for 10 minutes, and then immersed in sulfuric acid with a mass concentration of 100g / L for pickling. The nuts are pickled at 65°C for 45 minutes. The nuts are stirred and turned over in time during the pickling process. After the pickling is completed, the nuts are neutralized and washed with water to obtain pretreated nuts; the stabilizer includes 2kg of benzotriazole solution, 15kg of alkylphenol polyoxyethylene ether and 12kg of ammonium chloride solution, which are mixed in sequence; the concentration of the benzotriazole solution is 1mmol / L, and the mass concentration of the ammonium chloride solution is 20g / L;

[0057] S2. Hot-dip galvanizing: The pre-treated nuts are preheated at 300°C and immersed in a plating agent for 5 minutes. After being taken out, they are quickly hot-dip galvanized at 440°C; the plating agent includes 6.5kg potassium carbonate, 25kg zinc chloride, 50kg triethylamine, 12kg benzyl acetone, 9kg sodium polyoxyethylene ether sulfate, and 11kg 1-butyl-3-methylimidazolium chloroaluminate;

[0058] S3. After the galvanizing is completed, take the nut out of the zinc solution, put it into water and quickly cool it to room temperature, then immerse it in chromate passivation solution for passivation for 30 seconds to obtain a galvanized aviation anti-loosening nut. Comparative Example

[0059] Comparative Example 1

[0060] A galvanizing treatment process for aviation anti-loosening nuts, which is different from Example 1 in that no stabilizer is added to pre-treat the nuts during the pickling process in this comparative example.

[0061] Comparative Example 2

[0062] A galvanizing treatment process for aviation anti-loosening nuts, which is different from Example 1 in that the stabilizer added in this comparative example is an ammonium chloride solution with a mass concentration of 25g / L.

[0063] Comparative Example 3

[0064] A galvanizing treatment process for aviation anti-loosening nuts, which is different from Example 1 in that no plating aid is added for dipping during the galvanizing process in this comparative example.

[0065] Comparative Example 4

[0066] A galvanizing treatment process for aviation anti-loosening nuts, which is different from Example 1 in that no organic amine compound is added to the plating solution in this comparative example.

[0067] Comparative Example 5

[0068] A zinc plating treatment process for aviation anti-loosening nuts, which is different from Example 1 in that an equal amount of water is used in the plating solution in this comparative example instead of the ionic liquid.

[0069] Performance Testing

[0070] Detection Methods

[0071] Detection of coating surface performance: The appearance and covering capacity of the coating on the electroplating solution prepared in the embodiment and the comparative example and the nut after electroplating treatment were measured by visual inspection and gloss measurement. The visual inspection method considers the color and roughness of the coating surface. The glossiness is measured by a gloss meter at a refraction angle of 60°.

[0072] Corrosion resistance: According to GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", the time when no white corrosion products appear in the neutral salt spray test is recorded;

[0073] Plating bonding ability test: Use a grid cutter to scratch small grids on the surface of the test sample from the horizontal and vertical directions of the galvanized nuts, with an interval of 1mm, and each scratch line should be deep enough to reach the substrate; use a soft brush to gently brush the test sample surface 5 times backward and 5 times forward along the two diagonals of the grid pattern, use 3M tape or tape of equivalent effectiveness to firmly stick the small grid to be tested, and use an eraser to vigorously wipe the tape to increase the contact area and strength between the tape and the tested area; firmly grasp one end of the tape, and quickly tear off the tape in the vertical (90°) direction, and observe the surface with a magnifying glass. Experimental rating standard parts table 1.

[0074] Table 1 Rating criteria for bonding test

[0075] Grading illustrate 0 The edges of the cut are completely smooth, and there is no peeling on the edges of the lattice 1 There is a small amount of coating peeling off at the intersection of the cuts, but the cross-cut area affected cannot be more than 5% 2 The coating has fallen off at the intersection of the cuts or along the edges of the cuts, and the affected cross-cut area is significantly greater than 5%, but not significantly greater than 15% 3 The coating has partially or completely fallen off in large pieces along the cut edge, or has partially or completely fallen off in different parts of the grid, and the affected cross-cut area is significantly greater than 15%, but not significantly greater than 35% 4 The coating is peeling off in large pieces along the cut edge, or some squares are partially or completely peeling off, and the affected cross-cut area is significantly greater than 35%, but not significantly greater than 65%. 5 The degree of peeling exceeds level 4

[0076] Table 2 Test results

[0077] Coating surface properties Glossiness Corrosion resistance time / h Coating bonding ability Example 1 Uniform, smooth and bright surface 189.38 128 0 Example 2 Uniform, smooth and bright surface 185.24 125 0 Example 3 Uniform, smooth and bright surface 187.67 126 0 Example 4 Smooth surface, good gloss 194.45 142 0 Example 5 Smooth surface, improved brightness 195.12 148 0 Example 6 Smooth surface, high gloss 196.89 151 0 Example 7 Bright surface, with passivation layer 198.76 155 0 Comparative Example 1 There are traces of corrosion on the surface and the gloss is uneven 150.34 90 2 Comparative Example 2 The surface is slightly rough and the luster is dull 145.67 85 1 Comparative Example 3 The surface is peeling and the gloss is poor 130.23 75 3 Comparative Example 4 The surface has cracks and low gloss 160.12 100 1 Comparative Example 5 Uneven surface, average glossiness 155.45 95 1

[0078] Combining Examples 1-3 and Comparative Example 1 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1. The addition of the stabilizer can protect the surface of the nut, provide a better adhesion surface for subsequent coating, and improve the performance of the zinc coating.

[0079] Combining Examples 1-3 with Comparative Example 2 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 2. Using ammonium chloride as a single component as a stabilizer cannot provide sufficient protection, resulting in poor performance of the zinc coating and poor process stability.

[0080] Combining Examples 1-3 with Comparative Example 3 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3, indicating that the use of a plating aid can help enhance the bonding force between the zinc-plated layer and the nut substrate, thereby improving the corrosion resistance of the zinc-plated layer.

[0081] Combining Examples 1-3 with Comparative Example 4 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 4, indicating that organic amine compounds can help improve the bonding ability of the zinc layer during the galvanizing process, thereby improving the various properties of the coating.

[0082] Combining Examples 1-3 with Comparative Example 5 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 5. The ionic liquid has higher stability. Its application in the plating solution can help the zinc coating to adhere better and form a high-quality, corrosion-resistant zinc coating.

[0083] It can be seen from Examples 1-6 and Table 2 that the experimental data of Examples 4-6 are better than those of Examples 1-3, indicating that the addition of dithiosulfate succinic acid to the plating solution can promote the stable and uniform deposition of zinc ions on the nuts, which not only improves the adhesion of the coating, but also forms a dense and uniform coating, thereby enhancing the stability of the zinc plating layer of the nuts.

[0084] Combining Example 1 with Example 7 and Table 2, it can be seen that the test data of Example 7 are better than those of Example 1, indicating that further passivation treatment of the galvanized layer can further improve the corrosion resistance of the coating.

[0085] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A galvanizing process for aviation anti-loosening nuts, characterized in that: The steps include: S1. After the nuts have been preliminarily degreased, they are immersed in a stabilizer for a period of time, and then immersed in a pickling solution for pickling at 50-80° C. for 30-60 min. During the pickling process, the nuts are stirred and turned over in time. After the pickling is completed, the nuts are neutralized and washed with water to obtain pretreated nuts; The pickling liquid is sulfuric acid with a mass concentration of 100-200 g / L; the stabilizer includes benzotriazole solution, nonionic surfactant and ammonium chloride solution; S2. Hot dip galvanizing: preheat the pretreated nuts, control the temperature at 200-300°C, immerse them in a plating agent for 5-8 minutes, take them out and quickly hot dip galvanize them at 438-443°C; S3. After the galvanizing is completed, the nut is taken out from the zinc solution and quickly cooled to room temperature to obtain a galvanized aviation anti-loosening nut; The plating aid comprises the following raw materials in parts by weight: 5-8 parts of potassium carbonate, 20-30 parts of zinc chloride, 40-60 parts of organic amine compounds, 10-14 parts of zinc plating brightener, 8-10 parts of polyoxyethylene ether sodium sulfate, 10-12 parts of ionic liquid and 1-3 parts of dimercaptosuccinic acid.

2. The galvanizing process for aviation anti-loosening nuts according to claim 1, characterized in that: The stabilizer comprises the following raw materials in parts by weight: 1-3 parts of benzotriazole solution, 15-20 parts of nonionic surfactant and 10-15 parts of ammonium chloride solution.

3. The galvanizing process for aviation anti-loosening nuts according to claim 1, characterized in that: The benzotriazole solution is prepared by dissolving benzotriazole in dimethylformamide, and its concentration is 0.8-1.0 mmol / L. The mass concentration of the ammonium chloride solution is 20-25 g / L.

4. The galvanizing process for aviation anti-loosening nuts according to claim 1, characterized in that: The ionic liquid is 1-butyl-3-methylimidazolium chloroaluminate.

5. The galvanizing process for aviation locknuts according to claim 1, characterized in that: The organic amine compound is triethylamine.

6. The galvanizing process for aviation locknuts according to claim 1, characterized in that: After cooling to room temperature in step S3, the surface of the nut is further passivated by immersing it in a passivation solution for 30-40 seconds and drying it naturally; the passivation solution is chromate.

Citation Information

Patent Citations

  • Preservative treatment method for bolt

    CN110373622A

  • Hot galvanizing antiknock agent and preparation method thereof

    CN112962042A

  • Pickling solution and pickling method of metal product

    CN115261871A